2014
DOI: 10.1007/s00122-014-2394-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of bulked segregant analysis and microarrays reveals SNP markers pinpointing a major QTL for resistance to Phytophthora capsici in pepper

Abstract: Bulked segregant analysis (BSA) using Affymetrix GeneChips revealed candidate genes underlying the major QTL for Phytophthora capsici resistance in Capsicum. Using the candidate genes, reliable markers for Phytophthora resistance were developed and validated. Phytophthora capsici L. is one of the most destructive pathogens of pepper (Capsicum spp.). Resistance of pepper against P. capsici is controlled by quantitative trait loci (QTL), including a major QTL on chromosome 5 that is the predominant contributor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 55 publications
6
61
0
2
Order By: Relevance
“…Recent reports have suggested that the major resistance QTL is located on chromosome 5 [22,23] and that CaDMR1 is highly associated with this QTL, but functional validation has not been reported. Among the 12 examined DEGs (Figure 7), six DEGs ( XLOC_021142 , XLOC_021386 , XLOC_021757 , XLOC_021821 , XLOC_021928 and XLOC_022272 ) were on chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have suggested that the major resistance QTL is located on chromosome 5 [22,23] and that CaDMR1 is highly associated with this QTL, but functional validation has not been reported. Among the 12 examined DEGs (Figure 7), six DEGs ( XLOC_021142 , XLOC_021386 , XLOC_021757 , XLOC_021821 , XLOC_021928 and XLOC_022272 ) were on chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CaDMR1 , a candidate gene that encodes a homoserine kinase, was reported to be highly associated with the major QTL Pc5.1 [22]. Additionally, a single nucleotide polymorphism marker (SNP) on chromosome 5, Phyto5NBS1, was reported to be highly associated with resistant/susceptible traits against low virulence P. capsici strains [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Tissues sampled from the phenotypic extremes are pooled first, and then, a single DNA/RNA/protein isolation is performed; or DNA/RNA/protein is isolated first from each extreme individual, and then, an equal amount of the extraction from each individual is bulked. As the two bulking methods for DNA analysis do not give significantly different results (Liu et al ., ), bulking before extraction is more cost‐effective.…”
Section: Samples: Sampling Bulking and Multiplexingmentioning
confidence: 99%
“…The examples of BSA based on DNA/RNA/chip are summarized in Table . The method has been used to study a dozen of recessive mutants in maize (Liu et al ., ), leaf rust in wheat (Forrest et al ., ), sulphur and selenium contents in Arabidopsis thaliana (Becker et al ., ), salt resistance in cotton (Rodriguez‐Uribe et al ., ), bean common mosaic virus in common bean (Bello et al ., ), Phytophthora root rot in pepper (Liu et al ., ) and photosynthetic traits in poplar (Wang et al ., ).…”
Section: Applications: Genetics Genomics and Crop Improvementmentioning
confidence: 99%
“…SNPs are thus rapidly replacing traditional markers such as RFLP and SSR, and SNPs are now widely used in the construction of animal and plant genetic linkage maps. The BSA + gene chip method can quickly detect the genetic differences between two different phenotypes 22,23 . The SNP mutation and its chromosomal segment are more accurate than genome-wide gene mapping.…”
mentioning
confidence: 99%